Modeling the inter-phase region of high voltage transformers - Zainuddin, Hidayat; Lewin, P.L.; Mitchinson, P.M. (2011)
In large oil-filled power transformers, pressboard and paper in conjunction with oil are used throughout to provide electrical insulation. Microscopic views have shown that pressboard insulation is a fibrous and porous structure with a non-homogeneous surface. The porosity of pressboard can result in impurities within the oil being drawn into the oil-impregnated pressboard. The material properties and geometry of pressboard thus lead to a complex oil-pressboard interface. A 2-D model of oil-pressboard interface considering the porous and non-homogeneous of pressboard has been constructed using Finite Element Analysis software, COMSOL Multiphysics. This paper discusses the mathematical equations used to study the electric double layer (EDL) at the oil-pressboard interface where the oil is in a stationary condition. Subsequently, the simulation results of non-equilibrium charge density profile at the interface are also presented.